Applicability of ARFI elastography in the evaluation of canine prostatic alterations detected by b-mode and Doppler Ultrasonography - Cintra, C. A. [UNESP]; Feliciano, M. A. R.; Santos, V. J. C. [UNESP]; Maronezi, M. C. [UNESP]; Cruz, I. K. [UNESP]; Gasser, B. [UNESP]; Silva, P. [UNESP]; Crivellenti, L. Z.; Uscategui, R. A. R. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2020)
The aim of this study was to assess the applicability of ARFI elastography for the complementary diagnosis of canine prostatic alterations. Twenty-two healthy dogs and 45 with prostatic alterations were diagnosed by the association of general and specific physical exams. Complete blood count, B-mode and Doppler ultrasound were performed. For the elastography study, tissue homogeneity and deformity were verified using the elastogram, and the shear velocities of the left and right lobes of all prostates were obtained. The change in tissue homogeneity was observed in 62.2% of the animals, while the shear speed was significantly higher in dogs with prostatic alterations, with a cut-off point > 2.35m/s as an indication of change. All animals in both groups were non-deformable. It was concluded that ARFI elastography is capable of providing qualitative and quantitative results that assist in the diagnosis of canine prostatic alterations in a non-invasive way.
Keywords: dogs; prostatic changes; ARFI elastography